Early Proterozoic calc-alkaline and Middle Proterozoic tholeiitic dyke swarms from Central-Eastern Argentina: Petrology, geochemistry, Sr-Nd isotopes and tectonic implications - Iacumin, M. (2001)
The Rio de La Plata craton in Argentina (Azul and Tandil regions) is characterized by Early Proterozoic (2·0 Ga) calc-alkaline and Middle Proterozoic (1·6 Ga) tholeiitic dyke swarms intruding the crystalline basement involved in the Transamazonian Orogeny (2·2-1·9 Ga). The calc-alkaline dykes have andesitic and rhyolitic compositions and trend east-west, whereas the tholeiitic dykes mainly trend N30°W and are represented by basalts with low (0·9-1·7 wt %) and high TiO2 (up to 3·7 wt %). The calc-alkaline dykes have primitive mantle (PM)-normalized trace element patterns enriched in Rb, Ba, K, La, Ce and Nd, and significant negative Nb and Ti anomalies. These dykes are characterized by εt(Nd) values of - 3 to - 4, similar to those of the EMI mantle component. Low-TiO2 tholeiitic dykes have low incompatible-element (IE) contents and PM-IE patterns with slightly positive or negative Nb spikes. They have variable εt(Nd) values (-0·5 to 12·1), which mainly reflect derivation from a depleted source mantle. High-TiO2 tholeiitic dykes have more enriched IE-PM patterns and are characterized by εt(Nd) values (-1·4 to -7·5) typical of an enriched source mantle. Chemical and isotopic data and melting modelling indicate that both calc-alkaline and tholeiitic dykes originated by different melting degrees of a heterogeneous source mantle, the variable IE enrichment of which may have occured in Late Archaean to Early Proterozoic times. The emplacement of the calc-alkaline dykes is associated with the transtensional stage of the Transamazonian Orogeny, whereas the tholeiitic dykes reflect extensional tectonics succeeding the Transamazonian event. The calc-alkaline and tholeiitic dykes are similar in emplacement age and characteristics to metamorphosed granites and volcanic rocks outcropping within the Namaqua fold belts of southwestern Africa (Richtersveld and Witberg-Aggeneys-Gamsberg provinces); this may indicate that the Rio de La Plata craton and southwestern Africa were contiguous in Early-Middle Proterozoic times.